``Vergine come l'acqua de' maccheroni'': ``lingua affettiva'' and people's humour in the observations noted down by Niccolo Tommaseo on the Crusca Veronese - Caserio, Lucia (Romanica Olomucensia, 2019)
The paper shows Tommaseo's interest in popular humour, in the ironic and parodic usage of Tuscan parlances, and, more generally, in the expressive potentialities of the Italian language. His sensitivity to the ``lingua affettiva'' emerges right from his early lexicographical studies, as the original notes made about what is known as the Crusca veronese, which are presented here, illustrate. This research consisted of copying every single note handwritten by Tommaseo on the first volume of the dictionary, tracing each note back to his Crusca reference word and comparing each note with Tommaseo's other lexicographic and non-lexicographic works. From within this corpus of more than one thousand notes, the most significant ones regarding some popular and humorous linguistic uses were selected, such as tropes, euphemisms, and proverbs. Popular language was one of Tommaseo's main fields of investigation, as witnessed by the Canti Popolari edition. In notes such as Bariglione donna berta e grossa, Bell'e ito - Bell'e morto _ ironico, and vergine come l'acqua de' maccheroni Tommaseo revealed the humorous and ironic shades of the popular Tuscan he observed during his ``interrogazioni''. For Tommaseo the linguistic analysis of the Crusca was an important step towards the composition of the Sinonimi and Tommaseo-Bellini. This is confirmed, on the one hand, by the large number of notes with a reference word synonym and, on the other hand, by the continuous re-use of the annotated materials. It can be concluded that popular humour was an early subject of investigation for Tommaseo, being destined to continue throughout his activity as a lexicographer.
Keywords: humour; irony; notes; Niccolo Tommaseo; Crusca veronese